1994
DOI: 10.1016/0370-2693(94)00924-4
|View full text |Cite
|
Sign up to set email alerts
|

The proton matrix element of the topological charge in quenched QCD

Abstract: We present preliminary results on the proton spin structure function at zero momentum, in the quenched approximation. Our calculation makes use of a nonperturbative means of determining the multiplicative renormalization of the topological charge density.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 11 publications
1
17
1
Order By: Relevance
“…In the QCD context values for κ q of order 5 have been reported in ref. [30] (where κ q is denoted by Z −1 ). Ideally one would like to use fermions to measure directly Table 1: Critical values of (β,v) based on the DR data for (β c G , β c H ) presented in ref.…”
Section: Numerical Implementationmentioning
confidence: 99%
“…In the QCD context values for κ q of order 5 have been reported in ref. [30] (where κ q is denoted by Z −1 ). Ideally one would like to use fermions to measure directly Table 1: Critical values of (β,v) based on the DR data for (β c G , β c H ) presented in ref.…”
Section: Numerical Implementationmentioning
confidence: 99%
“…Alternatively, one can exploit the anomalous divergence equation of the flavor singlet axial vector current. Using this approach, the singlet coupling G 1 A is extracted from the correlation function of the proton propagator and the topological charge density [11,12,13]. Although this "topological method" circumvents the computationally expensive calculation of disconnected (fermionic) contributions, it has some intrinsic difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6]. An unquenched study using a geometrical definition of topological charge density has been reported in Ref.…”
mentioning
confidence: 99%
“…However an estimate may be obtained from the nonperturbative determination of the multiplicative renormalization of q L in quenched QCD, performed in Ref. [6], supplemented with relatively easier analytical two loop calculations of the only graphs containing fermion lines among those contributing to the two-point gluonic function with an insertion of q L . The evaluation of the other coefficients should be simpler, d qψ can be obtained from a one loop calculation, while γ 3 requires a two loop calculation in dimensional regularization.…”
mentioning
confidence: 99%